Wŏnhyo: Buddhist Commentator Par Excellence - Buswell, Robert E. (Journal of Korean religions, 2017)
Wŏnhyo (617–686) is best known within the Korean tradition as pilgrim, philosopher, mystic, thaumaturge, proselytist, and even touchstone of Korean unification ideology. But all these roles pale next to his importance as a commentator. In this proclivity, Wŏnhyo emulates intellectuals active within most traditional civilizations, where much of spiritual and religious understanding was conveyed through commentarial writing. Wŏnhyo's range of scholarly endeavor covered the whole gamut of East Asian Buddhist materials and the hundred or so works attributed to this prolific writer, over twenty of which are extant, find no rivals among his fellow Korean exegetes. The vast majority of Wŏnhyo's works are explicitly commentaries, and even those writings which are not are still strongly exegetical in character. The East Asian Buddhist tradition itself also treats Wŏnhyo principally as a commentator, as seen, for example, in the Song Gaoseng zhuan's (Song biography of eminent monks) inclusion of Wŏnhyo's biography in the section on "doctrinal exegetes" (yijie), together with a number of other Korean scholiasts who played important roles in the development of the learned schools of Sinitic Buddhism. In his virtuosity at manipulating the commentarial form, Wŏnhyo may be viewed not simply as a paragon of Korean scholarly achievement but as someone who was emblematic of the highest achievements of the Sinographic Buddhist tradition as a whole. This paper will explore the characteristics of Korean Buddhist commentary and examine the question of why Wŏnhyo used scriptural exegesis as the main vehicle for conveying his philosophical and spiritual insights.